2019
DOI: 10.47963/ajthm.v1i1.137
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of emotional labour among employees in the hospitality industry in Accra, Ghana

Abstract: The purpose of this study was to investigate the determinants of emotional labour among frontline employees in Ghanaian hotels. Specifically, the study identified the determinants of emotional labour which were hypothesized to have significant effects on emotional labour. A total of 205 frontline employees participated in the paper-pencil survey. The questionnaires contained items measuring individual, situational and organisational factors of emotional labour. The results indicated that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…While evidence abounds on the significance of emotional labour (Blankson-Stiles-Ocran et al , 2019; Côté and Miners, 2006; Fellner et al , 2012; Lartey, 2018), there exists little research on the effects of deep, surface and genuine acting on job satisfaction (Brotheridge and Grandey, 2002; Grandey, 2000), especially among hotel frontline workers in an emerging economy setting (Tagoe and Quarshie, 2017). Even so, the findings of such studies have been inconclusive (Lartey, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While evidence abounds on the significance of emotional labour (Blankson-Stiles-Ocran et al , 2019; Côté and Miners, 2006; Fellner et al , 2012; Lartey, 2018), there exists little research on the effects of deep, surface and genuine acting on job satisfaction (Brotheridge and Grandey, 2002; Grandey, 2000), especially among hotel frontline workers in an emerging economy setting (Tagoe and Quarshie, 2017). Even so, the findings of such studies have been inconclusive (Lartey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies on genuine acting and job attitudes, including job satisfaction, are rare. Studies conducted within the hotel industry have focused on determinants/antecedents of emotional labour, looking at the individual, organisational and situational factors that influence employee emotional labour (Blankson-Stiles-Ocran et al , 2019; Choi et al , 2019; Khetjenkarn and Agmapisarn, 2020). It is argued that the higher the class of the hotel, the higher and more effective the organisational display rules (Igbojekwe, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies consistently found that burnout percentages were much higher in developing countries than in developed countries [9], especially in Sub-Saharan Africa [7]. Another study conducted in South Korea reported that about 11% of all workers handling angry clients had experienced depression [6] A study in Ghana in Sub-Saharan Africa found that 91.1% of healthcare workers reported experiencing moderate to high rates of emotional exhaustion [18]. In Ethiopia, the prevalence of emotional exhaustion was more than half among Nurses [19].…”
Section: Discussionmentioning
confidence: 77%
“…The study found that the age and gender of the participant, department, experience, adequacy of staffing, work demand, high workload, cadre, and poor communication from managers on policy were associated with emotional disturbances. In Ghana, the practice environment of the nurses explained 39.6% of the variance in emotional exhaustion [18]. Similarly, in Brazil, a study found that nurses who experienced verbal and physical abuse and were concerned about workplace violence for the past 12 months had considerably higher risks of presenting high weariness, such as emotional exhaustion, depersonalization, and low professional accomplishment [ [11].…”
Section: Discussionmentioning
confidence: 99%